2014
DOI: 10.1182/blood-2014-01-552307
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 12 chronic lymphocytic leukemia cells exhibit upregulation of integrin signaling that is modulated by NOTCH1 mutations

Abstract: Key Points Trisomy 12 CLL cells exhibit upregulated integrin signaling and enhanced VLA-4-directed adhesion and motility. The increased expression of β2-integrins on trisomy 12 CLL cells is modulated by intercurrent NOTCH1 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
53
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 31 publications
11
53
1
1
Order By: Relevance
“…Given the strong link between proliferation and mutagenesis, the greater replication seen in trisomy-12+ B-CLL is consistent with the suggestion that trisomy-12 is a driver mutation which facilitates the accrual of further downstream mutations (33). Heightened growth of trisomy-12+ clones is also in agreement with recent findings that trisomy-12+ B-CLL express elevated CD38 in blood (143). Interestingly, two recent studies found B-CLL with trisomy-12 (or del11q22+) to express elevated levels of insulin growth factor receptor 1 (IGF-1R) (144, 145).…”
Section: Discussionsupporting
confidence: 91%
“…Given the strong link between proliferation and mutagenesis, the greater replication seen in trisomy-12+ B-CLL is consistent with the suggestion that trisomy-12 is a driver mutation which facilitates the accrual of further downstream mutations (33). Heightened growth of trisomy-12+ clones is also in agreement with recent findings that trisomy-12+ B-CLL express elevated CD38 in blood (143). Interestingly, two recent studies found B-CLL with trisomy-12 (or del11q22+) to express elevated levels of insulin growth factor receptor 1 (IGF-1R) (144, 145).…”
Section: Discussionsupporting
confidence: 91%
“…Tiziana D'Agaro, 1 Michaela Cerri, 2 Annalisa Chiarenza, 3 Kari G. Chaffee, 4 Adalgisa Condoluci, 5 Giovanni D'Arena, 6 Michele Spina, 7 Francesco Zaja, 8 Gabriele Pozzato, 9 Francesco Di Raimondo, 3 Davide Rossi, 5 Giovanni Del Poeta, 10 …”
unclassified
“…The peculiar clinical relevance of IGHV mutations in tris12 CLL might be related to a different pathobiology occurring in this subset, mainly involving B cell receptor-related microenvironment-driven pro-survival mechanisms rather than mechanisms ascribed to genetic lesions, 12 such as del13q, typically determining CLL cell survival via upregulation of the BCL2 antiapoptotic protein. Albeit the lack of independent clinical impact of NOTCH1 and SF3B1 mutations need to be confirmed in a prospective series, these findings add to other clinical and phenotypic peculiarities of tris12 CLL, 4,8 thus making a distinction between this CLL subset and the classical CLL.…”
mentioning
confidence: 99%
“…The expression of the CD18 variant in patients' B cells is even lower than that of the wild-type form [40]. By contrast, a CLL subgroup of patients harboring trisomy 12 (approximately 16% of CLL patients) show an important increase of LFA-1 and other integrins, associated with high cell proliferation and lymph node infiltration [41] [42]. These data do not clarify the role of LFA-1 in disease progression in CLL and suggest a complex interplay with other adhesion molecules and signaling pathways.…”
Section: Lfa-1 In Chronic Lymphocytic Leukemiamentioning
confidence: 97%